ESTIMATES OF THE STOCKS OF OIL SARDINE AND MACKEREL IN THE; PRESENT FISHING GROUNDS OFF THE WEST COAST OF INDIA - Sekharan, K V (Indian Journal of Fisheries, 2011)
During last decade the oil sardine fishery recorded remarkably high patches on the west coast. On the other hand, the mackerel fishery declined steeply in the nineteen-sixties, touching the lowest known levels, in contrast to most other fisheries of the west coast. The percentage of oil sardine in the all India marine fish landings was 32 in 1968, as against 16 in 1958, the corresponding values for mackerel being 2 and 16. This has focussed attention on the need for quick estimates of the maj;mtude of these populations. One approach for this would be to survey the areas occupied by these two species through acoustic and other means. Another approach would be to use the known population parameters and mathematical models to yield estimates of the populations. The latter method is adopted here.